HUBUNGAN TERITORIALITAS WARUNG LESEHAN TERHADAP SPACE CENTERED TERMINAL CONDONG CATUR - Nova Purnama Lisa (Jurnal MEDIAN Arsitektur dan Planologi, 2013)
The existence of an terminal involves many aspects of reality. Aspects of physical and non-physical has an equally important role to support activities in the inter-city bus station. Various activities will be followed by the formal sector, informal sector provides a typical pattern where the city bus station. The research provides on connections territoriality warung lesehan space centered. Territoriality affects the physical setting and activities of the regional bus terminal on warung lesehan activity. By doing observation phase analysis technique using mapping centered place and person centered mapping. Place centered mapping used to determine the characteristics and the amount of space used physical setting warung lesehan as territoriality or restrictions. Person centered mapping used to determine the movement and circulation disorders buyers who do the movement and activity in the terminal building Condong Catur Yogyakarta. The result of this method, and then conducted observations to determine the effect of territoriality on the physical setting warung lesehan. Traders in the Condong catar terminal, tends to mark their territory by tagging a fixed element for use in a long period of time. setting behavior is generated by a combination of events and places. Therefore it can be said that the physical setting has a reciprocal connection with a variety of behaviors that occur in these settings.